Training process design options in elite sprint skiing - Golovachev, A. I.; Kolykhmatov, V. I.; Shirokova, S. V.; Gorbunova, E. A. (Theory and Practice of Physical Culture, 2018)
The study analyzes the training process design options for elite ski sprint, with a special emphasis on the customizable controlled muscular loads that are demonstrated to be of the highest positive effect on the key bodily energy generation systems in competitive process. Experimental work under the study was run in the sprinters` regular training process. Sampled for the study were the 24-29 year-old elite sprinters (n=7) with a practical competitive experience gained in the 2013-2017 World Championships and 2010-2014 Olympic Games, who were also qualified and trained for the 2018 Winter Olympics in PyeongChang. The sample annual training cycle was modified to include a variety of categorical customizable controlled muscular loads. The study data and analyses showed that the 4-5 to 7-8 ms customizable controlled muscular loads with intensities above the anaerobic threshold and accelerations in the finishing stage are of the highest training effect on the oxidizing/ lactate energy generation system functionalities.